منهج الإمام القرافي في الرد على النصارى من خلال كتابه: الأجوبة الفاخرة عن الأسئلة الفاجرة - Hassan, Arafat Ahmed Moqbel (Al-Zahra: Journal for Islamic and Arabic Studies, 2023)
This research aims to show the critical personality of Imam Al-Qarafi, through his criticism of the Bible, which is an aspect that occupied the interest of contemporary researchers, both Muslims and Christians. From the legacy based on explanation and repetition, and starting towards a new vision that is directly related to the text, from it and back to it. In my research, I relied on the analytical descriptive approach in extracting information and results.